USING GREEN VALUE CHAIN AND VALUE STREAM TECHNOLOGIES TO REDUCE COSTS - Mithal Kreem Kadhim AL- Zubady; Ahmed Hassan Ali AL –Mamoori (Scholar Express Journals, 2024)
This research aims to shed light on the basic concepts of the sustainable value chain and Value Stream Technologies and to explain their role in increasing productivity, rationalizing costs and time, improving quality, enhancing sustainability, conserving energy, providing a safe and clean environment for workers and reducing the waste of the production process by identifying and analyzing activities and drawing a value stream map of the current situation in an attempt to identify the most important problems suffered by the economic unit to identify the areas available for development and address the shortcomings in the current situation value stream map and drawing a future value stream map. The deductive approach was used in the theoretical aspect of the research to reach the latest findings of the world in the field of the sustainable value chain and the value stream and their relationship to reducing the costs of economic existence. The inductive and analytical approach was used to research its practical side by using the statistical side to study the relationship of impact and correlation between the sustainable value chain and the value stream and cost reduction . Among the most important conclusions reached in this research is that There is a strong correlation between the green value chain, the value stream and the value stream method can make a positive contribution to achieving environmental sustainability as the value stream highlights the environmental waste arising from the unnecessary use of resources or materials released into the air, water or land that can harm human health and the environment. this means that the value stream makes significant contributions to achieving good results in environmental performance and the performance of operations .
Keywords: performance; environmental; value